Knowledge, Attitudes, and Practice Around HIV/AIDS and other STIs Among Syrians: A Cross-Sectional Study - Alibrahim, Hidar; Swed, Sarya; Bohsas, Haidara; Albakri, Khaled; Sawaf, Bisher; Elsayed, Mohamed (International Journal of Medical Students, 2023)
Background: Over 1 million new Sexual transmitted disease (STIs) are acquired daily throughout the globe, according to WHO data, with the majority of cases being asymptomatic. In Syria, statistics on STI awareness, attitude, and practice are few, and there is little information on Syrians' sexual and reproductive health concerns. The present research aims to determine which individuals factors best predict knowledge, attitudes, and behaviours about HIV/AIDS and other STIs in a Syrian population. Method: In the Syrian governorates between August 15 and September 16, 2022, a descriptive community-based cross-sectional survey was carried out. Syrian nationality, male or female, aged at least 18 years, citizen of any Syrian governorate, and willingness to engage in the survey were the study's inclusion criteria. Based on a previous study, a modified online semi-structured questionnaire was made on Google Form and used to collect the data. The questionnaire was divided into five main section that socio-demographic information, knowledge and practice relating STIs, knowledge and practice relating HIV/AIDS, attitude toward HIV/AIDS and attitude toward STIs. Results: The research involved 1076 individuals in total. More over half (55%) of them were women, with the majority (86%) of them being between the ages of 18 and 30. Only 739 respondents (67%) were aware of voluntary counselling and testing (VCT), and only 35% were aware of the means by which HIV infection may be prevented. The most often mentioned AIDS/HIV-related statistic was that those who have several sex partners have a greater chance of contracting HIV (92%). Furthermore, just 66% and 44%, respectively, of respondents knew how STDs are transmitted. In general, individuals' understanding of STDs was rated at 56%. Furthermore, 50% of the individuals had a positive attitude about the STD information. We used a logistic model to tease out the role of demographics and found that men were 1.43 times more likely to be aware of AIDS/HIV than women were. Additionally, residents of cities were 1.42 times more likely than residents of rural areas to be knowledgeable about STDs. Conclusion: According to this research, Syrians' knowledge, attitudes, and behaviors about STIs, HIV, and other diseases were generally insufficient. This provides definitive evidence that HIV programmes need to verify that Syrian people have access to basic information about HIV/AIDS and other STIs. As a result, the health organizations should conduct both international and local helpful interventions in order to address this medical problem and enhance the awareness of the Syrian community about HIV/AIDS and other STIs illnesses as soon as possible.